Table of Content - - (Journal of Humanities & Social Sciences, 2023)
Table of Content:1. Attitudes of university youth towards emigration in light of the war on Syria Tishreen University students as a modelMrs. Celine J. Shaheen2. Designing women's fashion that combines traditional fashion lines in the Kingdom of Saudi Arabia with artistic and contemporary schoolsCo-Prof. Arwa Daoud Khomayyis3. Benefiting from the aesthetics of the pop art school in recycling used environmental and artistic materials to produce artistic handicraftsDr. Nashwa Mohamed Issam Abd El-Aziz, Dr. Rasha Hassan Hosny Salem , Dr. Nagwa Kamel Mohamed Bosila4. Islamic Waqf in Yemen and its Economic EffectsMrs. Thekra Mohammed Al-Hattami5. The Implications of the Activating Defense Law No.13 of 1992 on Human Rights in Jordanian Society - The Corona pandemic as a modelDr.Dalal Shawkat Alodainat , Prof. Salim Ahmad Alquisi6. The Role of the British Advisor Charles Belgrave in the Making of the Modern State of Bahrain (1926 - 1957): A Historical StudyDr. Sharaf Mohamed Ali AlMezaal7. Role of Family Upbringing in Preparing Girls for the Marital Life Requirements in Contemporary Saudi Society(A study on a sample of newly married women in the Kingdom of Saudi Arabia from the different the western, eastern, southern, and northern regions)Dr. Amani Abdulaziz Afghani
Keywords: The Journal of Human and Social Sciences